Kecenderungan Kepribadian Neurotisme Dan Perilaku Merokok - Putra, Adik; Suhadianto, Suhadianto (Persona:Jurnal Psikologi Indonesia, 2017)
Abstract            This study aims to determine the relationship between the tendency kepriadian neuroticism with smoking behavior. This study is a coresional study that aims to determine the relationship between the tendency of neurotic personality with smoking behavior. The study involved 180 young adults with age range 20 to 40 years who behaved smoking. Sampling is done by incidential sampling technique. The measuring instrument used to collect research data is the Scale of Personality Trend of Neurotism and the Scale of Smoking Behavior compiled by researchers in Likert scale type. The data of this research were analyzed using Pearson Product Moment correlation analysis technique. From the results of data analysis, it can be concluded that there is a very significant positive relationship between the tendency of personality of neurotism and smoking behavior shown by p = 0,000 (p <0,01) and correlation coefficient value r = 0,400, hence can be interpreted the higher score the personality trends of a person's neuroticism are also higher in smoking behavior.              Keywords: Personality Trends of Neuroticism, Smoking Behavior